Catherine of Siena's wisdom on discernment and her reception of scripture - Diana L. Villegas (Acta Theologica)
Catherine of Siena’s wisdom on discernment represents a significant development in the history of this essential Christian theme. Her teaching is the fruit of personal wisdom rather than formal study as she was an uneducated lay woman in fourteenth century Italy. In this article I show how Scripture was central to Catherine’s wisdom. First I show that she was exposed to Scripture primarily orally and that she assimilated what she heard through her life of prayer and relationship with God. I describe the central biblical themes at the heart of her teaching on discernment, namely growth in charity and capacity for truth, and I show how these are related to her wisdom on discernment. I then examine how Catherine applied her teaching through an analysis of a letter to Pope Gregory XI.